2021
DOI: 10.22231/asyd.v17i4.1400
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de un arancel ad valorem sobre importaciones de carne de cerdo en México

Abstract: El objetivo fue evaluar el efecto de la aplicación de un arancel de 20% aprobado por México en junio de 2018, a importaciones de carne de cerdo en canal procedentes de Estados Unidos, mediante un modelo de programación no lineal con datos de 2017. El país se dividió en ocho regiones productoras y consumidoras: Noroeste, Norte, Noreste, Centro-Oeste, Centro-Este, Sur, Oriente, Península y dos puntos de internación de importaciones, Punto de internación uno, Punto de internación dos. El análisis se realizó en pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Since Mexico is an importer of pork, achieving efficiency and competitiveness in this sector is crucial. [ 9 ] emphasize the role of possible import tariffs on pork as a protective measure for the sector. The latter authors report that a 20% tariff would increase domestic production by 0.4% (4,774 tons), reduce imports by 18.9% (19,141 tons), decrease consumption by 0.06% (14,367 tons), and reduce the Net Social Value by -0.1% (-$309,050,545 USD)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Mexico is an importer of pork, achieving efficiency and competitiveness in this sector is crucial. [ 9 ] emphasize the role of possible import tariffs on pork as a protective measure for the sector. The latter authors report that a 20% tariff would increase domestic production by 0.4% (4,774 tons), reduce imports by 18.9% (19,141 tons), decrease consumption by 0.06% (14,367 tons), and reduce the Net Social Value by -0.1% (-$309,050,545 USD)…”
Section: Resultsmentioning
confidence: 99%
“…The study of [ 8 ], concluded that a subsidy to the supply function of pork carcass would improve the benefit to society by increasing production and protecting consumers. Similarly, the latter authors evaluated the application of a 20% ad valorem tariff, concluding that the sector is sensitive to such tariff and the current policy protects national producers; however, it has a negative impact on both importers and consumers [ 9 ], in a market with a deficit in pork supply. According to [ 10 ], pork production is an economic sector that has a total multiplier of 3.40, which strategically positions it as a driving force of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…El modelo de equilibrio espacial de precios requirió utilizar funciones de oferta y demanda inelásticas; funcionalmente, dependientes de la cantidad tanto demandada como ofertada, que en la literatura se conocen como funciones inversas de demanda y funciones inversas de oferta (Hernández et al, 2020;Rebollar et al, 2020). La función inversa de la demanda (es decir, en la que el precio, es la variable dependiente, fue una función de la cantidad demandada; en este caso, esta última, fue la variable independiente) para la región i fue:…”
Section: Ecuacionesunclassified
“…Además, este impuesto también se puede presentar en su modalidad de arancel ad valorem, el cual se puede expresar como un porcentaje fijo sobre el valor de la mercancía que se intercambia, en este caso, la carne de pollo en canal y actúa como mecanismo de protección de la producción nacional y regional y como desprotección a consumidores internos (Rebollar et al, 2020).…”
Section: Introductionunclassified